St Louis Cathedral Rear Historical Sketch Book and Guide to New Orleans - E. M. Law / Lilienthal (Wikimedia Commons, 1885)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Licence Public domain via Wikimedia Commons
Keywords: Histoire; iconographie; gravure; photographie; Wikimedia Commons